Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The problem:

Let $\tau(n)$ denote the Ramanujan $\tau$-function and $\sigma(n)$ be the sum of the positive divisors of $n$. Show that $$ (1-n)\tau(n) = 24\sum_{j=1}^{n-1} \sigma(j)\tau(n-j).$$

I'm afraid I don't even know how to start on this one.. My main problem is the $\tau$ function is defined as the coefficients of the $q$-series of the modular form $\Delta$, but that isn't (at least to my knowledge) very helpful in handling it. The properties that we have are all of a multiplicative nature (i.e., $\tau$ is multiplicative and $\tau(p^{a+2}) = \tau(p)\tau(p^{a+1}) - p^{11}\tau(p^a)$) which don't seem particularly well suited in a problem involving a sum.

Any hints, even just how to get started, would be greatly appreciated. Thanks!


As per Matt E's message, one can define, for any modular form $f$, an operator $\delta$ so that $\delta f = 12\theta f - 12E_2f$, where $\theta = q\frac{d}{dq}$. We wish to look at $\delta\Delta$. We have

\begin{align*} \delta\Delta &= 12\theta\Delta - 12E_2\Delta\newline &= 12\theta\left(\sum_{n=1}^\infty \tau(n)q^n\right) - 12E_2\Delta\newline &= 12q\left(\sum_{n=1}^\infty n\tau(n)q^{n-1}\right) - 12E_2\Delta\newline &= 12\left(\sum_{n=1}^\infty n\tau(n)q^n\right) - 12E_2\Delta. \end{align*} Now $\delta\Delta$ is a cusp form of weight 14, of which there are none that are non-zero. Thus we must have $$ 12\left(\sum_{n=1}^\infty n\tau(n)q^n\right) = 12E_2\Delta.$$ Thus we may simplify a little and plug in the a series representation of $E_2$ to find $$ \sum_{n=1}^\infty n\tau(n)q^n = (1 - 24\sum_{n=1}^\infty \sigma(n)q^n)\sum_{n=1}^\infty \tau(n)q^n.$$ Expanding the right hand side, and simplifying some more gives $$ \sum_{n=1}^\infty n\tau(n)q^n = \sum_{n=1}^\infty \tau(n)q^n - 24\sum_{n=1}^\infty \sigma(n)q^n\sum_{n=1}^\infty \tau(n)q^n,$$ so we have $$ \sum_{n=1}^\infty n\tau(n)q^n - \sum_{n=1}^\infty \tau(n)q^n = - 24\sum_{n=1}^\infty \sigma(n)q^n\sum_{n=1}^\infty \tau(n)q^n.$$ The end of the tunnel is starting to appear, as the left hand side looks quite nice at this point. We settle both sides into a single sum, so that we may match the coefficients on the left and right hand sides easily. We have $$ \sum_{n=1}^\infty \tau(n)(n - 1)q^n = - 24\sum_{n=1}^\infty \left(\sum_{j=1}^{n-1} \sigma(j)\tau(n-j)q^n\right),$$ so multiplying both sides by $-1$ and matching up the coefficients gives $$ \tau(n)(n - 1) = - 24 \left(\sum_{j=1}^{n-1} \sigma(j)\tau(n-j)\right)$$ for all $n\geq 1$, as desired.

share|cite|improve this question
up vote 5 down vote accepted

Apply the operator $\Delta$ discussed in this question to the modular form $\Delta$ (sorry for the conflict of notation vis-a-vis $\Delta$!). The result is a modular form of weight $14$. What can you say about it?

share|cite|improve this answer
I believe I've come across some progress, which I've editted in. I'll continue to think about this, and thanks for the answer! I have not seen the $\Delta$ operator before, so definitely would not have thought of this. – Alex Nov 22 '11 at 7:47
@Alex: Dear Alex, Try differentiating $\Delta$ in its series form (so that $\tau(n)$ appears directly in your answer) rather than in its product form. Regards, – Matt E Nov 22 '11 at 7:53
Wow! That worked out so smoothly! Though it begs the question, what is the $\delta$ operator? Thanks again! – Alex Nov 22 '11 at 8:29
@Alex: Dear Alex, It's part of the general theory of Rankin--Cohen brackets. I think it's easiest to understand from an automorphic point of view, rather than the more classical modular forms point of view. But that's the topic of another question ... ! Regards, – Matt E Nov 22 '11 at 8:32

This result can be generalized : Let $f$ be the following product : $$f(x)=\prod_{n=1}^{+\infty}{\left(1-x^n\right)^{a_n}}=\sum_{n=0}^{+\infty}{p(n)x^n}$$ By taking the logrtihmic derivitive of $f$ we obtain :

$$\frac{f'(x)}{f(x)}=-\sum_{n=1}^{+\infty}{na_n\frac{x^{n-1}}{1-x^n}}=-\frac{1}{x}\sum_{n=1}^{+\infty}{na_n\frac{x^n}{1-x^n}}$$ with $$\sum_{n=1}^{+\infty}{na_n\frac{x^n}{1-x^n}}=\sum_{n=1}^{+\infty}{na_n\left(\sum_{m=1}^{+\infty}{x^{nm}}\right)}=\sum_{n=1}^{+\infty}{\left(\sum_{d|n}{da_d}\right)x^n}$$ Thus : $$f'(x)=-\frac{f(x)}{x}\left(\sum_{n=1}^{+\infty}{\left(\sum_{d|n}{da_d}\right)x^n}\right)$$ and so $$\sum_{n=0}^{+\infty}{np(n)x^{n}}=-\left(\sum_{n=0}^{+\infty}{p(n)x^n}\right)\left(\sum_{n=1}^{+\infty}{\left(\sum_{d|n}{da_d}\right)x^n}\right)$$

A Cauchy product gives then the recursion formula $$p(0)=1$$ $$p(n)=\frac{-1}{n}\sum_{k=1}^n{p(n-k)\left(\sum_{d|n}{da_d}\right)}$$

(sorry form my approximative english... again)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.